Membrane potential governs calcium influx into microvascular endothelium: integral role for muscarinic receptor activation - Behringer, Erik J. (J Physiol, 2015)
KEY POINTS: Endothelial function in resistance vessels entails Ca(2+) and electrical signalling to promote vasodilatation and increase tissue blood flow. Whether membrane potential (V (m)) governs intracellular calcium concentration ([Ca(2+)](i)) of the endothelium remains controversial. [Ca(2+)](i) and V (m) were evaluated simultaneously during intracellular current injection using intact endothelial tubes freshly isolated from mouse skeletal muscle resistance arteries. [Ca(2+)](i) did not change during hyperpolarization or depolarization under resting conditions. However in the presence of 100 nM ACh (∼EC(50)), [Ca(2+)](i) increased during hyperpolarization and decreased during depolarization. These responses required extracellular Ca(2+) and were attenuated by half with genetic ablation of TRPV4 channels. In native microvascular endothelium, half‐maximal stimulation of muscarinic receptors enables V (m) to govern [Ca(2+)](i) by activating Ca(2+)‐permeable channels in the plasma membrane. This effect of V (m) is absent at rest and can be masked during maximal receptor stimulation. ABSTRACT: In resistance arteries, coupling a rise of intracellular calcium concentration ([Ca(2+)](i)) to endothelial cell hyperpolarization underlies smooth muscle cell relaxation and vasodilatation, thereby increasing tissue blood flow and oxygen delivery. A controversy persists as to whether changes in membrane potential (V (m)) alter endothelial cell [Ca(2+)](i). We tested the hypothesis that V (m) governs [Ca(2+)](i) in endothelium of resistance arteries by performing Fura‐2 photometry while recording and controlling V (m) of intact endothelial tubes freshly isolated from superior epigastric arteries of C57BL/6 mice. Under resting conditions, [Ca(2+)](i) did not change when V (m) shifted from baseline (∼−40 mV) via exposure to 10 μM NS309 (hyperpolarization to ∼−80 mV), via equilibration with 145 mm [K(+)](o) (depolarization to ∼−5 mV), or during intracellular current injection (±0.5 to 5 nA, 20 s pulses) while V (m) changed linearly between ∼−80 mV and +10 mV. In contrast, during the plateau (i.e. Ca(2+) influx) phase of the [Ca(2+)](i) response to approximately half‐maximal stimulation with 100 nm ACh (∼EC(50)), [Ca(2+)](i) increased as V (m) hyperpolarized below −40 mV and decreased as V (m) depolarized above −40 mV. The magnitude of [Ca(2+)](i) reduction during depolarizing current injections correlated with the amplitude of the plateau [Ca(2+)](i) response to ACh. The effect of hyperpolarization on [Ca(2+)](i) was abolished following removal of extracellular Ca(2+), was enhanced subtly by raising extracellular [Ca(2+)] from 2 mm to 10 mm and was reduced by half in endothelium of TRPV4(−/−) mice. Thus, during submaximal activation of muscarinic receptors, V (m) can modulate Ca(2+) entry through the plasma membrane in accord with the electrochemical driving force.